Instructions for dancing ebook - Yoon, Nicola (2021)
AN INSTANT #1 NEW YORK TIMES BESTSELLER "A charming, wholehearted love story that's sure to make readers swoon."— Entertainment Weekly "Nicola Yoon writes from the heart in this beautiful love story."—Good Morning America “It’s like an emotional gut punch—so beautiful and also heart-wrenching."— US Weekly In this romantic page-turner from the author of Everything, Everything and The Sun is Also a Star, Evie has the power to see other people’s romantic fates — what will happen when she finally sees her own? Evie Thomas doesn't believe in love anymore. Especially after the strangest thing occurs one otherwise ordinary afternoon: She witnesses a couple kiss and is overcome with a vision of how their romance began . . . and how it will end. After all, even the greatest love stories end with a broken heart, eventually. As Evie tries to understand why this is happening, she finds herself at La Brea Dance Studio, learning to waltz, fox-trot, and tango with a boy named X. X is everything that Evie is not: adventurous, passionate, daring. His philosophy is to say yes to everything—including entering a ballroom dance competition with a girl he's only just met. Falling for X is definitely not what Evie had in mind. If her visions of heartbreak have taught her anything, it's that no one escapes love unscathed. But as she and X dance around and toward each other, Evie is forced to question all she thought she knew about life and love. In the end, is love worth the risk?